Neurofeedback as neuroempowerment technique for affective regulation and interoceptive awareness in adolescence: preliminary considerations applied to a psychogenic pseudosyncope case - Balconi, Michela; Angioletti, Laura; Crivelli, Davide (Frontiers in Rehabilitation Sciences, 2023)
Revisions of classical models of acute stress response spectrum and defence cascade process might represent a valuable background for the interpretation of the link between affective reactions, traumatic experiences, and Psychogenic pseudosyncope (PPS) events in childhood and across the lifespan. Indeed, associations between subjective emotional life, early exposure to distressing and/or traumatic events, and PPS have fuelled a debate on potential causes of occurrence and recurrence of such a peculiar clinical manifestation. At the same time, such background suggests that empowering stress management and affective regulation skills could be the target for neurorehabilitation interventions aiming at reducing the severity of symptomatology and/or improving awareness and management of pseudosyncopal spells. Specifically, neuro/biofeedback-based empowerment of self-regulation skills, associated to an increased interoceptive increased awareness, could be a promising complement to classical psychological therapies. Starting from the presentation of a paediatric PPS clinical case, the present work discusses the relevance of assessing affective appraisal and autonomic reactivity in individuals suffering from PPS episodes and introduces a novel potential neuroempowerment protocol aimed at improving self-regulation and stress management skills in adolescence based on a combined neurofeedback and embodied-awareness intervention. By capitalizing available evidence of the effects of neuromodulation and embodied practices on self-awareness/regulation across the life-span, the proposed protocol is based on neurofeedback-supported affective management training, as well as both contemplative and informal awareness exercises devised to be appealing and challenging even for younger patients.